2018
DOI: 10.1177/1474704918757551
|View full text |Cite|
|
Sign up to set email alerts
|

Do Men Produce Higher Quality Ejaculates When Primed With Thoughts of Partner Infidelity?

Abstract: Sperm competition theory can be used to generate the hypothesis that men alter the quality of their ejaculates as a function of sperm competition risk. Using a repeated measures experimental design, we investigated whether men produce a higher quality ejaculate when primed with cues to sperm competition (i.e., imagined partner infidelity) relative to a control prime. Men ( n = 45) submitted two masturbatory ejaculates-one ejaculate sample for each condition (i.e., sperm competition and control conditions). Eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…The target sample size for the study at conceptualization was 100 men. The target sample size was determined based on the primary aim of the study (within-subjects design; Pham et al, 2018). After 3 years of data collection (and before data analysis), a consensus was reached to stop data collection in May 2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The target sample size for the study at conceptualization was 100 men. The target sample size was determined based on the primary aim of the study (within-subjects design; Pham et al, 2018). After 3 years of data collection (and before data analysis), a consensus was reached to stop data collection in May 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Methodological information relevant to the current study aim is reported here. Full methodological details are also reported in the article by Pham et al (2018). All procedures were approved by the institutional review board of the university where data were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with previous research on mate retention (Buss et al, 2008; Lopes et al, 2016), this sample included only individuals in a romantic relationship with the opposite sex for at least 3 months. We invited prospective participants through: (1) Amazon Mechanical Turk (MTurk): interested and eligible individuals could access and complete an on-line survey, and those who completed the survey received U$2.50; (2) the Psychology Department Subject Pool at a large Midwestern U.S. university: interested and eligible individuals were provided a link to an online survey, and those who completed the survey received partial course credit upon completion (Lopes et al, 2017); and (3) advertising on bulletin boards on the campus of the same Midwestern U.S. university: interested individuals contacted the researcher, and those who met the participation criteria and agreed to participate were escorted to a private room to answer an in-person survey and received U$25 at the conclusion of the survey (Pham et al, 2018). The current article reports novel analyses of a subset of data from different projects.…”
Section: Methodsmentioning
confidence: 99%
“…Further, as a potential mechanism of cryptic female choice, exciting new research has demonstrated that sperm chemoattractants produced by eggs may facilitate gamete-mediated 'mate choice' in humans [101]. The study of adaptations to human sperm competition has traditionally bordered the fields of behavioural ecology and evolutionary psychology [102]. Now it seems that this fascinating area of research is reaching into the realm of reproductive biology in relation to the role that the FRT, specifically oviductal fluid and sperm chemoattractants, plays in determining postmating 'mate choice' outcomes.…”
Section: (B) Of Men and Women: Sperm Competition In Humansmentioning
confidence: 99%